Research progress on secure data deduplication in cloud - Jin-bo XIONG; Yuan-yuan ZHANG; Feng-hua LI; Su-ping LI; Jun REN; Zhi-qiang YAO (Tongxin xuebao)
In order to improve the efficiency of cloud storage and save the communication bandwidth, a deduplication mechanism for multi-duplicate of the same data in cloud environment was needed. However, the implement of the secure data deduplication was seriously hindered by the ciphertext in cloud. This issue has quickly aroused wide attention of academia and industry, and became a research hotspot. From a security standpoint, firstly the primary cause and the main challenges of secure data deduplication in cloud environment was analyzed, and then the deduplication system model as well as its security model was described. Furthermore, focusing on the realization mechanism of secure data deduplica-tion, the thorough analyses were carried on and reviews for the related research works in recent years from content-based encryption, proof of ownership and privacy protection for secure deduplication, then the advantages and common prob-lems of various key technologies and methods were summed up. Finally, the future research directions and development trends on secure data deduplication in cloud was given.